Analisis Tingkat Kualitas Aek Macom di Kecamatan Lembah Sorik Marapi Kabupaten Mandailing Natal - Mahmudi, Yasir; Prarikeslan, Widya (TSAQOFAH, 2025)
This study aims to analyze the water quality of Aek Macom in Lembah Sorik Marapi Subdistrict, Mandailing Natal Regency, based on physical, chemical, and biological parameters, and to identify the spatial distribution of its pollution levels. Water samples were collected from three different locations and tested in a laboratory using physical parameters (Total Suspended Solids/TSS), chemical parameters (pH, Dissolved Oxygen/DO, Biochemical Oxygen Demand/BOD, Chemical Oxygen Demand/COD, nitrate, and total phosphate), and biological parameters (Fecal Coliform). The test results showed TSS values ranging from 2.12–3.71 mg/L, pH 4.35–5.11, DO 2.21–7.15 mg/L, BOD 2.56–12.76 mg/L, COD 11.32–46.90 mg/L, nitrate 24.18–44.00 mg/L, total phosphate 0.44–1.08 mg/L, and Fecal Coliform 89–113 MPN/100 mL. All results were then compared to the water quality standards set in Government Regulation No. 22 of 2021 concerning Environmental Protection and Management. Using the pollution index method, it was determined that the pollution index value was <6, indicating that Aek Macom falls under the lightly polluted category for Class II designation, which includes freshwater fish cultivation, water recreation facilities/infrastructure, and agricultural irrigation. The light pollution was identified in several villages, such as Maga Dolok, Pasar Maga Subdistrict, and Maga Lombang. These findings provide critical insights for water quality management in the area to prevent further degradation and ensure the sustainability of the local ecosystem.